2001
DOI: 10.1359/jbmr.2001.16.2.386
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal and Pubertal Skeletal Changes Contribute Predominantly to the Differences in Peak Bone Density Between C3H/HeJ and C57BL/6J Mice

Abstract: Previous studies have shown that 60 -70% of variance in peak bone density is determined genetically. The higher the peak bone density, the less likely an individual is to eventually develop osteoporosis. Therefore, the amount of bone accrued during postnatal and pubertal growth is an important determining factor in the development of osteoporosis. We evaluated the contribution of skeletal changes before, during, and after puberty to the development of peak bone density in C3H/HeJ (C3H) and C57BL/6J (B6) mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
87
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 39 publications
7
87
0
Order By: Relevance
“…Studies comparing the bone shape and quality of C3H/HeJ (C3) and C57BL/ 6J (B6) mice found several key differences in both geometry and femoral strength. C3 mice have higher femoral bone mineral density and thicker cortices compared to B6 mice, although both strains fall within the normal range of bone mineral densities for mice [19,38]. C3 mice also had a smaller cross-sectional area, but twice the bone volume as compared to B6 [20].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Studies comparing the bone shape and quality of C3H/HeJ (C3) and C57BL/ 6J (B6) mice found several key differences in both geometry and femoral strength. C3 mice have higher femoral bone mineral density and thicker cortices compared to B6 mice, although both strains fall within the normal range of bone mineral densities for mice [19,38]. C3 mice also had a smaller cross-sectional area, but twice the bone volume as compared to B6 [20].…”
Section: Discussionmentioning
confidence: 81%
“…At E18.5 and P1, differences in bone size and shape between C3 and B6 femurs can already be seen [38,40]. By one month of age, C3 mice have a greater cortical bone width coupled with a smaller marrow cavity diameter than B6 femurs and these differences persist and become more exaggerated until one year of age [38,40]. Additionally, by 12 weeks of age, C3 femurs have thicker trabeculi and smaller trabecular separation compared to B6 femurs [41].…”
Section: Discussionmentioning
confidence: 99%
“…less than corresponding age-matched normal children (Woods et al 1997). Furthermore, we and others have shown that serum levels of IGF-I increase during puberty and correlate with BMD (Moreira-Andres et al 1995, Libanati et al 1999, Thorsen et al 1999, Richman et al 2001, Kasukawa et al 2003. Although recent studies provide evidence that both the variation in peak BMD and circulating levels of IGF-I are largely determined genetically (Harrela et al 1996, Recker & Deng 2002, Baldock & Eisman 2004, the direct experimental evidence for the hypothesis that genetic-dependent variation in IGF-I production is a major determinant of the variation in peak BMD seen in normal healthy individuals is lacking at the present time.…”
Section: Introductionmentioning
confidence: 74%
“…To assess quantitatively bone mass, architecture, and turnover, static and dynamic histomorphometric analyses were performed on female ⌬Igf1r and control littermates at 3 and 6 weeks of age, when the skeletal modeling in the mouse is very active (33). At these ages, the mutant and normal animals were indistinguishable in size and weight.…”
Section: Resultsmentioning
confidence: 99%